2015
DOI: 10.3892/or.2015.4517
|View full text |Cite
|
Sign up to set email alerts
|

CD151 knockdown inhibits osteosarcoma metastasis through the GSK-3β/β-catenin/MMP9 pathway

Abstract: Osteosarcoma (OS) is a primary bone malignancy with a high early metastatic propensity. It is crucial to find specific protein targets to develop therapeutic strategies against this lethal disease. Tetraspanin CD151 is involved in facilitating tumor metastasis. However, the role and molecular mechanism of CD151 in promoting OS metastasis remain enigmatic. In the present study, we used small interfering RNA (siRNA) to inhibit CD151 expression in highly metastatic OS cells and the results demonstrated that CD151… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…β‐catenin is a key molecule of the Akt signaling pathway, and migrates from cytoplasm to cell nucleus to activate the Akt pathway . Some members of the tetraspanin family have been reported to inhibit β‐catenin degradation . We have observed that TSPAN31 knockdown reduced the expression of Akt signaling pathway component β‐catenin.…”
Section: Resultsmentioning
confidence: 70%
“…β‐catenin is a key molecule of the Akt signaling pathway, and migrates from cytoplasm to cell nucleus to activate the Akt pathway . Some members of the tetraspanin family have been reported to inhibit β‐catenin degradation . We have observed that TSPAN31 knockdown reduced the expression of Akt signaling pathway component β‐catenin.…”
Section: Resultsmentioning
confidence: 70%
“…3B). The obtained zymogram showed that although there was no bands associated with function of MMP-2 (72 kDa) or MMP-9 (92 kDa) (both shown to be regulated by CD151 (Yanez-Mo et al, 2008;Zhang et al, 2016)), a clear CD151-dependent digestive activity, located at molecular weight of approx. 48 kDa, typical for MMP-13 was observed (Fig.…”
Section: Cd151 Is Involved In Regulation Of Promigratory and Proinvasmentioning
confidence: 94%
“…The proteomic analysis demonstrates that package proteins of exosomes are specific and are completely different from cell apoptosis by the release of apoptotic bodies [ 68 , 69 ]. The High Throughput Sequencing technology verifies that the miRNA is also subject to certain mechanisms rather than a random package of exosomes [ 70 ].…”
Section: Exosomes: New Intercellular Communicatorsmentioning
confidence: 99%
“…Furthermore, Tspan8 mediates tumor cell motility and invasion [ 72 , 90 ]. Tetraspanin CD151 has been shown to be involved in tumor cell motility, invasion, metastasis and angiogenesis [ 69 , 70 ]. CD9 is considered to be a tumor suppressor and facilitates tumor angiogenesis [ 76 , 91 ].…”
Section: Exosomal Tetraspanin Networkmentioning
confidence: 99%